2002
DOI: 10.1063/1.1479348
|View full text |Cite
|
Sign up to set email alerts
|

Formation of anion fragments from gas-phase glycine by low energy (0–15 eV) electron impact

Abstract: Dissociative electron attachment to pentaerythritol tetranitrate: Significant fragmentation near 0 eV Absolute partial cross sections for electron-impact ionization of CH4 from threshold to 1000 eV We have measured the formation of anion fragments in gas phase glycine (H 2 NCH 2 COOH) via dissociative electron attachment ͑DEA͒ reactions in the 0-15 eV electron energy range, using a monochromatic electron beam and mass spectrometric detection of the negative ions. By far the most intense product observed is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
3
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 25 publications
9
105
3
1
Order By: Relevance
“…The common feature in the DEA cross sections we observe between 1.18 and 1.27 eV has been seen previously in mass analyzed data in glycine, [17][18][19] alanine, 20 proline, 21 and tryptophan. 22 A similar feature appears in HCOOH.…”
Section: Amino Acidssupporting
confidence: 55%
See 1 more Smart Citation
“…The common feature in the DEA cross sections we observe between 1.18 and 1.27 eV has been seen previously in mass analyzed data in glycine, [17][18][19] alanine, 20 proline, 21 and tryptophan. 22 A similar feature appears in HCOOH.…”
Section: Amino Acidssupporting
confidence: 55%
“…Finally, we note that estimates of the total DEA cross sections at the 1.2 eV feature have been given elsewhere for glycine 18,19 ͑5 ϫ 10 −16 and ϳ10 −16 cm 2 ͒ and for alanine ͑1.5ϫ 10 −16 cm 2 ͒. 20 The reasons for these substantial overestimates have been discussed previously.…”
Section: Dea Cross Section Magnitudesmentioning
confidence: 99%
“…This shift is called sometimes the "solvation energy." Because of some uncertainties in this quantity, we present results of two calculations: one with 07001-p. 7 EPJ Web of Conferences 6 cluster for the geometry of Ref. [40] for two solvation energies, 0 and −0.2434 eV.…”
Section: Dr2013mentioning
confidence: 99%
“…From gas phase experiments, it was found that all the nucleobases [1][2][3][4], organic acids [5] and also amino acids [6][7][8] exhibit a hydrogen loss due to low-energy electrons. In biological environment, the anion (M−H) − can initiate further reactions leading to the cell damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation